BIMBINGAN KONSELING DI MADRASAH - Muhamad Irham (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This paper intends to offer a model - concept integrative - comprehensive guidance in MI that no format. The problem is analyzed based on the theory of Islamic education and the needs in MI. The results of the study showed that the concept of integrative - comprehensive in Counseling in MI education includes three main components, namely: 1) leadership/managerial; 2) learning, and 3) self-development. BK integrative-comprehensive services in MI involving parents. The issue of integration of knowledge in Islamic education contributed to the preparation of - concept model of integrative - comprehensive BK in MI. Characteristics of integrative - comprehensive model of BK in MI is no coherence in the programs, workforce, perosedur, and system services. This model was characterized to develop aspects of personality, social, academic/learning, career, and even decency students. Developed lesson plan format includes objectives so that learners are aware of the importance of gratitude to God Almighty. His knowledge, sincerity in seeking knowledge and practice it , willingness to perform and excel in their field, as well as internalized social attitudes on the basis of better knowledge and understanding of himself as God 's creatures, MI graduates are expected to create superior and ready to compete.